Paratexts as an Instrument of Power. German Translations of Icelandic Prose around 1900 - Lerner, Marion (CLINA: Revista Interdisciplinaria de Traducción, Interpretación y Comunicación Intercultural, 2019)
Josef Calasanz Poestion was an influential author and translator from Icelandic into German. Among his translations was the first Icelandic novel, which he published several times. His translations are always accompanied by a series of paratexts, in which the translator’s presence is unusually strong. In these texts, he provides his readers with extensive knowledge of Icelandic culture and literature and positions himself as an authority on Iceland. Through frequent references to other writings, which he incorporated into annotations, introductions and other peritexts, he produced an extensive array of epitexts. He not only positioned himself as a figure of pedagogical authority vis-à-vis his readers, but also towards the Icelandic nation. His attitude toward Iceland is that of the center toward the periphery and is marked by an intra-European exoticism and orientalism. Josef Calasanz Poestion fue un influyente autor y traductor del islandés al alemán. Entre sus traducciones se encuentra la primera novela islandesa, que publicó varias veces. Sus traducciones siempre van acompañadas de una serie de paratextos, en los que la presencia del traductor es atípicamente fuerte. En estos textos, proporciona a sus lectores un amplio conocimiento de la cultura y la literatura islandesas y se posiciona como una autoridad sobre Islandia. A través de frecuentes referencias a otros escritos, que incorporó en anotaciones, introducciones y otros peritextos, produjo una extensa gama de epitextos. No solo se posicionó como una figura de autoridad pedagógica ante sus lectores, sino también ante la nación islandesa. Su actitud hacia Islandia es aquella que va del centro hacia la periferia y está marcada por un exotismo y un orientalismo intraeuropeos.